Konsep Pembelajaran Perspektif Ibnu Khaldun dan Relevansinya pada Pembelajaran Bahasa Arab di Abad 21 - Ahmad Azhari; Zakiyah Arifa; Qulyubi Mahsan Nasukha Rais; Muhammad Hidayatullah (Universitas Yudharta Pasuruan, 2021)
This qualitative research aims to analyze the concept of learning Ibn Khaldun's perspective and its relevance to Arabic learning in the 21st century. The primary data source in the research is the Muqaddimah Ibnu Khaldun, while the Sukender data is in the form of documents, books, or articles related to the research subject. The findings in this study indicate that the learning theory proposed by Ibn Khaldun is Malakah and Tadrīj, while the learning methods he offers are the Tadarruj and Takrīr, Rihlah and Munāzarah Methods. After analyzing the method that Ibn Khaldun offered, the researcher found that the learning concept as outlined by Ibn Khaldun in his Muqaddimah book is relevant to Arabic learning in the 21st century, which demands that learning is student-centered. The learning method offered by Ibn Khaldun leads to an increase in the competence of students. The researcher finds that there is a relevance between the methods offered by Ibn Khaldun and the principles of learning Arabic in the 21st century. It is hoped this research can become a reference in the development of a particular study in Arabic learning in the 21st century.